CRIMINAL ACT OF MISUSE OF ELECTRONIC MONEY WHICH HAMS CUSTOMERS (CASE STUDY OF MEDAN FINANCIAL SERVICES AUTHORITY) - Zikirullah, Affan (Inspiring Law Journal, 2024)
In the last few years, many customers have been harmed by the actions of irresponsible people. People often take advantage of technological developments to take advantage of technology itself as a weapon (cybercrime). This type of crime then developed and became generally known as